Guided Haversian remodeling in acute bone trauma in rabbit ribia and mandible - Hong He (2018)
Objective: To search a better novae biomaterial applied to guide bone regeneration for promoting the healing of acute bone trauma by the experimental study of Haversian remodeling. Method: Circular bone defects of 5mm diameter were created in tibias and the corners of mandibles in 36 rabbits. The defects were covered with calcium alginate film (CAF) in the experimental group, collagen membrane (CM) and no membrane (blank) in the control groups respectively. Healing conditions were analyzed using gross inspection, and histological and immunohistochemical studies after 1, 2, 4, 6 and 8 weeks respectively. Results: The experimental group appeared more and earlier Haversian remodeling with osteoinductive factors leading to better bone regeneration. The control groups showed more macrophages with CM absorbed slowly, weak and delayed Haversian remodeling, and less osteoinductive factors (P < 0.05) in the early stage. Conclusions: Calcium alginate film, as a relatively cheaper biomaterial, provided better effect than the collagen membrane on guided bone regeneration, because of its better Haversian remodeling and more content of osteoinductive factors shown in this experiment.